Annual Reviews of Computational Physics IV - Stauffer Dietrich (World Scientific Pub Co Inc, 1996)
Quantum phenomena and methods are the core of this volume. It includes such topics as simulations of magnetic fields; quantum Monte Carlo on a lattice - the world line algorithm; computer simulation of quantum phenomena in nano-scale devices; and tight-bending molecular dynamics.